Effectiveness of Accounting Information Systems for Sales and Cash Receipts at Fox Hotel Pekanbaru - Ramadani, Nadia Fitri; Agustiawan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to assess the effectiveness of the sales and cash receipts accounting information system implemented at Fox Hotel, Pekanbaru. The success of an effective accounting information system is very important to support hotel operations, especially in ensuring the accuracy of transactions, accounting efficiency, and the timely presentation of financial reports. The research method used is descriptive qualitative with triangulation techniques through observation, interviews, and documentation. The results showed that the implementation of the accounting information system with the VHP (Visual Hotel Program) program for cash and credit sales transactions has been running quite well. However, there are still some obstacles, such as delays in the cash receipt process due to external factors, such as third-party payment platforms, and a lack of coordination between sections. This study concludes that in general, the system is effective, but improvements are still needed in the return system.